Proceedings of the 13th International Symposium on Multiscale, Multifunctional and Functionally Graded Materials 2014
DOI: 10.5151/matsci-mmfgm-193-f
|View full text |Cite
|
Sign up to set email alerts
|

Strain Gauge Sensor Comprised of Carbon Nanotube Yarn: Concept and Modeling

Abstract: Carbon nanotube yarns are micron-size fibers that contain thousands of intertwined carbon nanotubes in their cross sections and exhibit piezoresistance characteristics that can be tapped for sensing purposes. Sensor yarns can be integrated in polymeric and composite materials to measure strain through resistance measurements without adding weight or altering the integrity of the host material. This paper includes the details of novel strain gauge sensor configurations made of carbon nanotube yarn and the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Luo et al [20,21] modelled single-walled CNT into a 1D fibre with the potential application for mapping the stress/strain states of the embedded composite under different deformation modes such as tension, bending and compression. Abot et al [22,23] studied the piezo-impedance effect of a CNT yarn for strain sensing functionality. A behavioural study showed a parabolic negative piezoresistive response during most of the deformation phase and a linear positive piezoresistive response that preceded the failure of the CNT yarn.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [20,21] modelled single-walled CNT into a 1D fibre with the potential application for mapping the stress/strain states of the embedded composite under different deformation modes such as tension, bending and compression. Abot et al [22,23] studied the piezo-impedance effect of a CNT yarn for strain sensing functionality. A behavioural study showed a parabolic negative piezoresistive response during most of the deformation phase and a linear positive piezoresistive response that preceded the failure of the CNT yarn.…”
Section: Introductionmentioning
confidence: 99%